PENGAWASAN TERHADAP PENYALAHGUNAAN WEWENANG POLRI MENGADAKAN TINDAKAN LAIN MENURUT HUKUM YANG BERTANGGUNG JAWAB (DISKRESI) - Made Suteja (University of Udayana, 2013)
ABSTRACTFunction of control and authority of the Police of the Republic ofIndonesia related to the aspects of preemptive, preventive, and repressive. One ofduties of the Police of the Republic of Indonesia as the state's instrument and lawenforcer in maintain the law repressively to help the Department of Justiceespecially in the field of criminal law the Police as the investigator andinvestigating offrcer can carry out other action according to law which isresponsible or discretion.The formal legalistically arrangement about the police discretion inKUHAP (Article 5 subsection (1) letter a number 4 and Article 7 subsection (1)letter j) and the Law No.2 1n2002 about the Police of the Republic of Indonesia inArticle 16 subsection (1) letter I and subsection (2) and Article 18 subsection (1)and subsection (2) which is written and implicated widely so it makes this becomea blur norm of law, and it needs an interpretation in the application. The discretionarrangement seems to emerge the disharmonious of law norm. To avoid thedeviation of the discretion implementation in the future the norm arrangement hasto be harmonized through the law construction to the articles of the arrangementby reevaluating and reformulating them by the legislative institution.The type ofresearch to be used to research the substance of discretion bythe police in this scientific work is the normative law research or doctrinal lawresearch. Police discretion needs an internal and extemal monitoring from therelated institution including monitoring ftom the society especially the victim.Deviation of discretion will emerge a risk due to law and lawresponsibility by the person who does the discretion. The law responsible can be aresponsibility of criminal, civil Iaw and administration law. Deviation ofdiscretion action as the result of the wide range of discretion scope and there is nomeasurement or criterion of discretion forms that can be done by the Police as areference in action which is arranged in legislation.The study and analysis of police discretion upon the problems presented isreviewed by the law principles, expertise doctrine, formal basic and law theoriessuch as law system theory, law harmonious theory, progressive law theory,authority theory and monitoring theory. The theoretical perspective study issupported by empirical law materials and descriptive description of the writer.